Mobile Learning Design for Basic Programming Independent Learning - Elmi, Hafiz; Ganefri, Ganefri; Irfan, Dedy (Universitas Negeri Padang, 2020)
This study discusses about design of the self-learning mobile learning basic programming based on Android. Designed mobile learning material contains an abstract discussion of programming that is not visible invisible. This material was translated by concrete and to be more easily understood by students. The method used in the design of self-learning mobile learning is SDLC (System Development Life Cycle) waterfall, and use the process of UML (unified modeling language) with the use case diagram and flowchart. The results of this study indicate that the self-learning mobile learning basic programming is easy to use for students and teachers as instruction learning.